Pengaruh penerapan standar akuntansi pemerintah terhadap kualitas laporan keuangan pada dinas perindustrian dan perdagangan di kota tenggarong - Siti Ulfah; Anis Rachma Utary; Ferry Diyanti (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
This research is based on the mistakes in money report documentation because of the ineffective goverment standard accountant application. Therefore, money report documentation must be based on approved goverment accountant standard. This research result is to know and analyze is the goverment accountant standard effects the quality of money report on Industry and Trading Departement at Tenggarong City. This research is hoped can give benefit to organization in giving suggestion about how to improve the quality of money report, also gives knowledge more to the author and reader about the effect of goverment accountant standard to money report quality. This research had 47 respondents as sample to fill questionnaire and there were 31questionnaire which was filled well. Sampling technique collection was purposive sampling, and to determine the result of this research researcher used Partial Least Square (PLS). Based on research which was done on Industry and Trading Department at Tenggarong City can be concluded that goverment accountant standard (X) proved had significant positive effect and significant to money report quality (Y), it is based on hypothesis calculation result with sample original score as many as 0,547 and t-statistic as many as 3,732 1,64 which means goverment accountant standard has positive effect and significant to money report quality, stated that (Ha) is accepted.